Environmental water quality management of glyphosate-based herbicides in South Africa - Mensah, Paul Kojo (Rhodes University, Faculty of Science, Institute for Water Research, 2013)
Although the use of pesticides is necessary to meet the socio-economic needs of many developing countries, especially in Africa, side effects of these bio-active chemicals have contributed to contaminating aquatic and terrestrial ecosystems. Environmental water quality degradation by pesticides interferes with ecosystem health and poses numerous risks to aquatic life. In South Africa, glyphosate-based herbicides are frequently used to control weeds and invading alien plants, but ultimately end up in freshwater ecosystems. However, there are no South African-based environmental water quality management strategies to regulate these bio-active chemicals. Therefore, this study sought to provide a sound scientific background for the environmental water quality management of glyphosate-based herbicides in South Africa, by conducting both laboratory and field investigations. In the laboratory investigations, aquatic ecotoxicological methods were used to evaluate responses of the freshwater aquatic shrimp Caridina nilotica exposed to Roundup® at different biological system scales, and the responses of multiple South African aquatic species exposed to Roundup® through species sensitivity distribution (SSD). In the field investigations, the effect of Kilo Max WSG on the physicochemical and biological conditions of three selected sites in the Swartkops River before and after a spray episode by Working for Water were evaluated through biomonitoring, using the South African Scoring System version 5 (SASS5) as a sampling protocol. Both Roundup® and Kilo Max WSG are glyphosate-based herbicides. All the data were subjected to relevant statistical analyses. Findings of this study revealed that Roundup® elicited responses at different biological system scales in C. nilotica, while SSD estimates were used to derive proposed water quality guidelines for glyphosate-based herbicides in South Africa. The biomonitoring revealed that using glyphosate-based herbicides to control water hyacinth within the Swartkops River had a negligible impact on the physicochemical and biological conditions. Based on these findings, a conceptual framework that can be used for the integrated environmental water quality management of glyphosate-based herbicides in South Africa was developed as part of integrated water resource management (IWRM). The combined data sets contribute to a sound scientific basis for the environmental water quality management of glyphosate-based herbicides in South Africa.
Keywords: Water quality management -- South Africa; Water quality management -- Environmental Aspects -- South Africa; Herbicides -- Environmental aspects -- South Africa; Herbicides -- Toxicology -- South Africa; Water -- Glyphosate content -- South Africa; Water -- Pollution -- South Africa; Water quality -- Measurement -- South Africa; Water -- Analysis -- South Africa; Freshwater ecology -- South Africa; Integrated water development -- South Africa; Caridina -- Effect of pollution on -- South Africa